A Comprehensive Stylistic Analysis of Bariq Shafiee's Poetry Collection 'Stak' Across Five Layers: Phonological, Lexical, Syntactic, Rhetorical, and Ideological - Teymoor Malmir; Karima Mufradzada (Current Educational Review, 2026)
Bariq Shafiee (1931–2016) is among the founders of modern poetry in Afghanistan and one of the most influential figures of Dari Persian poetry in the twentieth century. The publication of 'Stak' in 1963 is considered the first independent modern Dari Persian poetry collection in Afghanistan and a turning point in contemporary Afghan literary history. Drawing upon Cyrus Shamisa's layered stylistics theory and employing a descriptive-analytical and statistical methodology, this study undertakes a comprehensive and in-depth examination of Bariq Shafiee's stylistic features across five layers: phonological, lexical, syntactic, rhetorical, and ideological. The statistical population comprises 25 poems from the 'Stak' collection, selected through purposive sampling. Findings reveal that, at the phonological layer, 92% of poems are composed in classical prosodic metres, with the poet's innovation concentrated primarily in rhyme and refrain schemes (64%). At the lexical layer, 34% of vocabulary belongs to the semantic domain of 'fire and explosion,' 26% to 'revolution and struggle,' and 20% to 'binary oppositions.' At the syntactic layer, repetition stands out as the most prominent stylistic marker, appearing 58 times across 25 poems (mean 2.32 per poem). At the rhetorical layer, metaphor accounts for the highest frequency at 27%. At the ideological layer, left-leaning anti-establishment ideology with emphasis on class justice forms the central core of the poet's worldview. This study demonstrates that all five layers in Bariq Shafiee's poetry exhibit organic and purposeful coherence, collectively serving to articulate a revolutionary ideology and create a fiery, dynamic poetic atmosphere